PERANCANGAN SISTEM INFORMASI PENDAFTARAN PASIEN RAWAT JALAN MENGGUNAKAN VISUAL BASIC.NET DI UPTD PUSKESMAS TANJUNGPURA - Opik Bastiar (Jurnal Teknik dan Manajemen Informatika, 2025)
UPTD Tanjungpura Public Health Center is an agency engaged in district or city health services that is responsible for carrying out health development in one or some sub-districts. Public health center need the existence of an information system to improve the quality of health services to patients seeking treatment at the public health center so that it runs well. At the UPTD Public Health Center Tanjungpura the data collection system in providing services to patients, drug data collection, prescriptions and reports are still done manually or not yet computerized. Design of an Outpatient Registration Information System which was made using the waterfall method with the components of system design tools in the form of Use Case Diagrams, Activity Diagrams and Class Diagrams. The implementation of the program used by the computer in the outpatient registration information system uses the Visual Basic.Net programming language. Hopefully the new system will make it easier for outpatient registration to be made to overcome the problems that exist in the Tanjungpura Public Health Center UPTD and patients also find it easy to get access to the integrated registration service at the public health center.